Drip irrigated Barley (Hordeum vulgare L.) in arid regions of South Tunisia: Plant Growth and Yield Parameters - Mohamed Thabet (Turkish Journal of Agriculture: Food Science and Technology)
Historically relegated to the status of “poor man’s bread” barley is one of widely cultivated crops in arid regions of south Tunisia for its grain and biomass used as an animal feed and other various purposes. Barley is incorporated into many types of home recipes. Harsh climate and frequent droughts are the great challenge for cereals production so farmers must supply irrigation in order to improve yields. Traditional irrigation techniques are widely used despite their low efficiency. Conversion to drip is encouraged by public services as a measure to save water resources, boost yields and as an adaptation measure to climate change that will cause more pressure on available water resources .The present paper presents results for drip irrigated barley in arid climate of South Tunisia. The study was undertaken at research farm of Institute of Arid Regions in Medenine and tried to replicate current farmer’s practices with the aim to facilitate their conversion to drip irrigation. For full drip irrigated barley (100% irrigation water requirements), following crop variables were recorded according to standard agronomic procedures as described in Daur et al. (2011): Plant height (m); Ears number by square meter at harvest; Number of grains per ear; 1000 grain weight (g); Biological yield (kg.m-2); Grain yield at harvest (g.m-2). Grain yield was 360.75g m-2 which corresponds to 3.61 ton ha-1and Biological yield was 1.014 kg m-2 for a total water amount of 225 mm. These values far exceed those obtained in rainfed agriculture.